A 5-year surveillance of healthcare-associated infections in a university hospital: A retrospective analysis. (April 2022) - Erdem, Ilknur; Yıldırım, Ilker; Safak, Birol; Karaali, Ritvan; Erdal, Berna; Ardic, Enes; Dogan, Mustafa; Kardan, M Enes; Kavak, Caglar; Sahin Karadil, Kubra; Yildiz, Emre; Topcu, Birol; et al.
Objectives: "Nosocomial infections" or "healthcare-associated infections" are a significant public health problem around the world. This study aimed to assess the rate of laboratory-confirmed healthcare-associated infections, frequency of nosocomial pathogens, and the antimicrobial resistance patterns of bacterial isolates in a University Hospital. Methods: A retrospective evaluation of healthcare-associated infections in a University Hospital, between the years 2015 and 2019 in Tekirdag, Turkey. Results: During the 5 years, the incidence densities of healthcare-associated infections in intensive care units and clinics were 10.31 and 1.70/1000 patient-days, respectively. The rates of ventilator-associated pneumonia, central line–associated bloodstream infections, and catheter-associated urinary tract infections in intensive care units were 11.57, 4.02, and 1.99 per 1000 device-days, respectively. The most common healthcare-associated infections according to the primary sites were bloodstream infections (55.3%) and pneumonia (20.4%). 67.5% of the isolated microorganisms as nosocomial agents were Gram-negative bacteria, 24.9% of Gram-positive bacteria, and 7.6% of Candida . The most frequently isolated causative agents were Escherichia coli (16.7%) and Pseudomonas aeruginosa (15.7%). The rate of extended-spectrum beta-lactamase production among E. coli isolates was 51.1%. Carbapenem resistance was 29.8% among isolates of P. aeruginosa, 95.1% among isolates of Acinetobacter baumannii, and 18.2% among isolates of Klebsiella pneumoniae . Colistin resistance was 2.4% among isolates of A. baumannii . Vancomycin resistance was 5.3% among isolates of Enterococci. Conclusion: Our study results demonstrate that healthcare-associated infections are predominantly originated by intensive care units. The microorganisms isolated from intensive care units are highly resistant to many antimicrobial agents. The rising incidence of multidrug-resistant microorganisms indicates that more interventions are urgently needed to reduce healthcare-associated infections in our intensive care units.